PENGARUH HARGA, KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA RM. MIE TAREMPA RUKO ROYAL SINCOM - Harinsari, Ferdania Nanda; syarif, Arman (Zona Manajerial: Program Studi Manajemen (S1), 2021)
This study aims to determine the effect of price, product quality, and service quality on purchasing decisions at RM. Mie Tarempa Ruko Royal Sincom. The method used is associative with a quantitative approach. Research data obtained by distributing questionnaires to 100 respondents. The results showed that price, product quality, and service quality had a positive and significant effect either partially or simultaneously on purchasing decisions for Mie Tarempa Ruko Royal Sincom.